Merck and Vioxx. (B), Merck settled claims for $4.85 billion - Elias, Jaan; Bagley, Constance E. ([London] : SAGE, 2016)
Backing off their strategy to fight every single claim, Merck & Co. reached a settlement with a steering committee of plaintiffs' attorneys in November 2007. According to the agreement, the company would pay $4.85 billion to settle most claims arising from its Vioxx medication. Merck stressed that the settlement was not a class action. In addition, Merck did not admit to any fault in its sale of Vioxx. Lawsuits that had already gone to verdict would not be affected by the settlement. This study details the process of the legal settlement.
Originally Published in: Elias, J., Hutchins, S., Nagy, A., Bagley, C. E., & Rae, D. W. (2008). Merck and Vioxx (B): Merck Settled Claims for $4.85 Billion. 08-017. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Merck & Co; Crisis management -- Case studies; Actions and defenses -- Case studies